Dissociation between area TE and rhinal cortex in accuracy vs. speed of visual categorization in rhesus monkeys - Li, Bing; Lowe, Kaleb; Chandra, Samarth; Chen, Gang; Eldridge, Mark A. G.; Richmond, Barry J. (Frontiers in Behavioral Neuroscience, 2024)
In real-world vision, objects may appear for a short period such as might occur in conjunction with visual search. Presumably, this puts a premium on rapid categorization. We designed a visual categorization task cued by briefly presented images to study how visual categorization is processed in an ethologically relevant context. We compared the performance of monkeys with bilateral area TE lesions, and those with bilateral rhinal cortex lesions, to control animals. TE lesions impaired the accuracy but not the speed of visual categorization. In contrast, rhinal cortex lesions didn't affect the accuracy but reduced the speed of visual categorization. A generalized drift-diffusion model (GDDM) with collapsing bounds was fitted to the data. The rate of drift was equivalent across all groups, but the decision bounds collapsed more slowly in the rhinal group than the other two groups. This suggests that, although evidence is accumulated at the same rate in all groups, the rhinal lesion results in slower decision making.